1983
DOI: 10.1029/ja088ia12p10145
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the spatial distribution of dayside cleft optical emissions

Abstract: An analysis of measurements of the 4278-A, 5200-A, 5577-A, and 6300-A emissions obtained from a rocket launch through the postnoon dayside cleft into the polar cap ionosphere is reported. The 4278-A and 5577-• emissions show a clearly defined decrease in intensity at the poleward.edge of the dayside particle precipitation, while the 5200-A emission extends well into the polar cap with only a slight decrease in intensity. The 6300-A emission displays a behavior intermediate between these extremes. The optical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

1984
1984
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 81 publications
0
4
1
Order By: Relevance
“…But Te could increase and thermal excita- tion could become important if there were a significant downward heat flux. In contrast, our results do not agree with previous combinations of observations and theory [Gault et al, 1981;Link et al, 1983] which dismiss the importance of thermal excitation. While we do not have correlative 6300-A intensities, they did not have correlative electron temperatures.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…But Te could increase and thermal excita- tion could become important if there were a significant downward heat flux. In contrast, our results do not agree with previous combinations of observations and theory [Gault et al, 1981;Link et al, 1983] which dismiss the importance of thermal excitation. While we do not have correlative 6300-A intensities, they did not have correlative electron temperatures.…”
Section: Discussioncontrasting
confidence: 99%
“…Although on the dayside, these observations have been in the winter hemisphere at such locations that the sun was well below the horizon. The high intensity regions, which are limited in latitude (1 to 5 ø) and extended in longitude (1 to 10 hrs), have been associated with either magnetospheric features, the cusp and cleft [Shepherd, 1979, and references therein], or ionospheric features, the morning and afternoon convection cells [Reiff et al, 1978]. The source of excitation for the atomic oxygen has been attributed to low energy electrons [Shepherd, 1979, and references therein].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Duboin et al [1984] also found that on the basis of temporal variability of ground-based observations of N I 5200 ]k and O I 6300 ]k, the N(2D) source is not the major source mechanism for O(1D). Link et al [1983] further argue against this process and point out that the need for this source in the dayglow is inconclusive. Also, the empirical relationship between O I 6300 ]k and the energetic electron flux found by Shepherd et al [1980] suggests that electron impact excitation is the main source of the red line.…”
Section: N(2d) + 02--> No + O(1d)mentioning
confidence: 99%
“…On the gross scale shown in Plate 1, the 557 nm images identify regions of auroral electron precipitation for which typical electron energies are several to many keV. In contrast, the 630 nm images identify regions of low-energy (E • 500 eV) electron precipitation [Shepherd et al, 1980;Murphree et al, 1983;Link et al, 1983]. Hence, the different wavelength bands lead to general information about the precipitating electrons spectral softness or hardness as well as the energy fluxes [Rees and Luckey, 1974].…”
mentioning
confidence: 99%